Pulsed‐Dye Laser Treatment of Port‐Wine Stains in Children: Useful Tips to Avoid General Anesthesia. Issue 5 (30th July 2017) - Alegre‐Sánchez, Adrián; Pérez‐García, Bibiana; Boixeda, Pablo
Abstract: Pulsed dye laser (PDL) treatment of port‐wine stains (PWSs) in children is a common procedure performed in most laser units. Pain assessment in our younger patients is a major concern, especially in those with extensive PWSs. The use of general anesthesia (GA) results in pain‐free treatment, but its effects on the developing brain are far from totally understood. Thus we propose some tips that avoid the use of GA in most of our young patients, including the use of topical anesthetics and cooling systems, large laser spot size and high frequencies, early and frequent treatment with parents present, and the "introduction" and "pressure" techniques, among others.